Overcoming The Feeling Of Insecure As An Idea In The Creation Of Painting Art - Puspayoga, Putu Gede; Kondra, I Wayan; Sucipta, I Wayan Adi; Suryadinata T. Y., Anak Agung Gde Trisna (Program Studi Seni Murni ISI Bali, 2024)
Insecurity is a feeling of discomfort or fear that is triggered by a feeling of dissatisfaction and uncertainty about one's capacities. Insecurity is a common problem that often occurs among society, especially today's young people, if it is not addressed it can disrupt productivity in living life, a lack of understanding and knowledge regarding insecurity and how to overcome this condition often causes this insecurity to be a taboo matter. The aim to be achieved in the creation of this work is to understand the efforts that can be made to overcome feelings of insecurity in the perspective of packaging the embodiment of a work of painting. The author will visualize the efforts to overcome this feeling of insecurity using a visual analogy approach in the meaning of a message that will be expressed as a work of painting. In its development, the author formulated several things, various efforts to overcome feelings of insecurity and a visual analogy approach technique in expressing expressions of efforts to overcome feelings of insecurity.